The dependence of cusp ion signatures on the reconnection rate - S. K. Morley; M. Lockwood; M. Lockwood (Annales Geophysicae, 2003)
The interpretation of structure in cusp ion dispersions is important for helping to understand the temporal and spatial structure of magnetopause reconnection. "Stepped" and "sawtooth" signatures have been shown to be caused by temporal variations in the reconnection rate under the same physical conditions for different satellite trajectories. The present paper shows that even for a single satellite path, a change in the amplitude of any reconnection pulses can alter the observed signature and even turn sawtooth into stepped forms and vice versa. On 20 August 1998, the Defense Meteorological Satellite Program (DMSP) craft F-14 crossed the cusp just to the south of Longyearbyen, returning on the following orbit. The two passes by the DMSP F-14 satellites have very similar trajectories and the open-closed field line boundary (OCB) crossings, as estimated from the SSJ/4 precipitating particle data and Polar UVI images, imply a similarly-shaped polar cap, yet the cusp ion dispersion signatures differ substantially. The cusp crossing at 08:54 UT displays a stepped ion dispersion previously considered to be typical of a meridional pass, whereas the crossing at 10:38 UT is a sawtooth form ion dispersion, previously considered typical of a satellite travelling longitudinally with respect to the OCB. It is shown that this change in dispersed ion signature is likely to be due to a change in the amplitude of the pulses in the reconnection rate, causing the stepped signature. Modelling of the low-energy ion cutoff under different conditions has reproduced the forms of signature observed. Key words. Ionosphere (particle precipitation) Magnetospheric physics (energetic particles, precipitating, magnetopause, cusp and boundary layers)